2018
DOI: 10.1039/c8cc00695d
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative evaluation of molecular meshingviasurface analysis with varying probe radii

Abstract: A novel method for the semi-quantitative evaluation of molecular meshing in molecular complexes and assemblies (SAVPR: surface analysis with varying probe radii) is proposed. SAVPR revealed that the extremely high stability of hexameric assemblies (nanocubes) is due to tight molecular meshing between the components in the assemblies, indicating the importance of van der Waals interactions in hydrophobic molecular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previously, we reported cube-shaped discrete molecular self-assemblies, i.e., nanocubes, from gear-shaped amphiphiles (GSAs) in water 16,17 . The main driving force of the self-assembly of the nanocubes is the hydrophobic effect, but weak intermolecular interactions such as dispersion 18 and cation-π 19 interactions also significantly contribute to the stability of the nanocubes. The accumulation of multiple weak interactions give rise to great thermal stability of the nanocubes, which do not disassemble into the monomers at all at even higher temperature than the boiling point of water 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported cube-shaped discrete molecular self-assemblies, i.e., nanocubes, from gear-shaped amphiphiles (GSAs) in water 16,17 . The main driving force of the self-assembly of the nanocubes is the hydrophobic effect, but weak intermolecular interactions such as dispersion 18 and cation-π 19 interactions also significantly contribute to the stability of the nanocubes. The accumulation of multiple weak interactions give rise to great thermal stability of the nanocubes, which do not disassemble into the monomers at all at even higher temperature than the boiling point of water 17 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyze the molecular meshing between the GSAs in the nanocubes, SAVPR (surface analysis with varying probe radii) 18 was carried out. SAVPR shows the distribution of the contact surface area as a function of contact distance.…”
Section: -D In CD 3 Odmentioning
confidence: 99%
“…In SAVPR, the distribution of contact surfaces between molecules with a contact distance for a given three‐dimensional structure (crystal structure or energy‐minimized structure) is calculated by changing the size of the probe sphere. Previous SAVPR studies on nanocubes and host–guest complexes indicated that contact surfaces with a separation of less than 1 Å are important for the vdW stabilization . The SAVPR profiles of the MM‐optimized structure of the four nanocubes (Figure ) are similar, but the BM nanocube has slightly more contact surface with a separation of less than 0.5 Å compared to the other nanocubes.…”
Section: Resultsmentioning
confidence: 81%
“…Previous SAVPR studies on nanocubes and hostguest complexes indicated that contact surfaces with as eparation of less than 1 are important fort he vdW stabilization. [10] The SAVPR profileso ft he MM-optimized structure of the four nanocubes ( Figure 4) are similar,b ut the BM nanocube has slightly more contact surface with as eparation of less than 0.5 compared to the other nanocubes.Contrary to the experimentalr esults, the molecular meshing of the GSAs in the p- MeOBM nanocube is less strong than in the BM nanocube. Thus it mightb ed ifficultt op recisely discussv ery small difference in the molecular meshing by SAVPR.…”
Section: Evaluation Of Molecular Meshingmentioning
confidence: 81%
See 1 more Smart Citation